2021
DOI: 10.3390/plants10102011
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium nirenbergiae (Fusarium oxysporum Species Complex) Causing the Wilting of Passion Fruit in Italy

Abstract: Passion fruit (Passiflora edulis Sims.) is an ever-increasing interest crop in Italy because it is mainly cultivated for its edible fruit and, secondly, as an ornamental evergreen climber. During the summer of 2020, two-year-old plants of purple passion fruit in one of the most important expanding production areas of Sicily (southern Italy) showed symptoms of yellowing, wilting, and vascular discoloration. Fusarium-like fungal colonies were consistently yielded from symptomatic crown and stem tissues. Five rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The third lineage includes five isolates that did not cluster with any of the reference species used for the phylogenetic analyses and that were defined as F. oxysporum sensu lato. Fusarium nirenbergiae belongs to the FOSC, and it is reported as a pathogen on saffron in China [30] and on passionfruit in Italy [41]. It was recently described as a pathogen in maize in China [19], and our study represents the first finding of this species as a maize pathogen in Italy.…”
Section: Discussionsupporting
confidence: 52%
“…The third lineage includes five isolates that did not cluster with any of the reference species used for the phylogenetic analyses and that were defined as F. oxysporum sensu lato. Fusarium nirenbergiae belongs to the FOSC, and it is reported as a pathogen on saffron in China [30] and on passionfruit in Italy [41]. It was recently described as a pathogen in maize in China [19], and our study represents the first finding of this species as a maize pathogen in Italy.…”
Section: Discussionsupporting
confidence: 52%
“…Sanna et al [29] investigated Fusarium species associated with post-emergence damping-off and root rot in maize and found that F. nirenbergiae caused a disease index of over 50% in some maize areas of Italy, as did F. verticilloides, F. annulatum and F. commune. Aiello et al [35] identified F. nirenbergiae as the cause of root rot and wilt in passion fruit plants. Zhao et al [36] identified it as the cause of wilt in maple trees (in China), and Moral-Lopez et al, [37] in almonds (in Portugal and Spain).…”
Section: Dry Root Weigth 2022 2023mentioning
confidence: 99%
“…The expansion of passion fruit cultivation faces several challenges, notably diseases that can lead to total crop loss. Passion fruit is susceptible to a variety of diseases caused by fungi, viruses, and bacteria, which can induce symptoms such as wilting, leaf spotting, and fruit rot, among others (Aiello et al 2021).…”
Section: Introductionmentioning
confidence: 99%